PENGARUH KEBIJAKAN HARGA, ATMOSFER TOKO DAN PELAYANAN TOKO TERHADAP PERILAKU IMPULSE BUYING KONSUMEN ROBINSON DEPARTMENT STORE SEMARANG - Herukalpiko, Diah Kenanga; Prihatini, Apriatni Endang; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2014)
This study aimed to test the influence of pricing policy, store atmospheric and store service on impulse buying behaviour of consumers in Robinson Department Store Semarang. The samples in this research are 100 customers who shop in Robinson Department Store Semarang. The author used SPSS 16.0 program to test the regression on the data analysis. And the study results indicate that pricing policy has a positive and significant influence on the impulse buying behavior of consumers, with coefficient determination is 36,4%, store athmospheric has a positive and significant influence on the impluse buying behavior of consumers, with coefficient determination is 32,2%, store service has a positive and significant influence on the impulse buying behavior of consumers, with coefficient determinaion is 71,2%, and pricing policy, store atmospheric and store service has a positive and significant influence on the impulse buying behavior of consumers, with the coefficient determination is72,2%. Results of this study indicate that in order to enhance the impulse buying behavior, Robinson Department Store Semarang should consider the pricing policy, store atmospheric and store service.